Transgenic parasites accelerate drug discovery - Rodriguez, Ana (2012)
Parasitic neglected diseases are in dire need of new drugs either to replace old drugs rendered ineffective because of resistance development, to cover clinical needs that had never been addressed or to tackle other associated problems of existing drugs such as high cost, difficult administration, restricted coverage or toxicity. The availability of transgenic parasites expressing reporter genes facilitates the discovery of new drugs through high throughput screenings, but also by allowing rapid screening in animal models of disease. Taking advantage of these, we propose an alternative pathway of drug development for neglected diseases, going from high throughput screening directly into in vivo testing of the top ranked compounds selected by medicinal chemistry. Rapid assessment animal models allow for identification of compounds with bona fide activity in vivo early in the development chain, constituting a solid basis for further development and saving valuable time and resources.